MAIN ASPECTS OF ENERGY CONSERVATION IN CIVIL ENGINEERING (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This scientific study is about the day-to-day increase in the world's energy resources, about the end of non-renewable, conventional energy sources(oil, gas, coal, etc.),the current state of use of non-traditional and new-generation energy sources (solar energy, wind energy, hydropower, biomass, etc.) in the countries of the world, information is given about the directions of energy conservation, the types of energy conservation measures, the consideration and analysis of energy conservation measures on the example of each system and devices that consume energy, the measures that should be carried out in energy conservation buildings.